1991
DOI: 10.1210/jcem-73-2-262
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Deletion Resulting in Frameshift as a Possible Cause of Complete Thyroxine-Binding Globulin Deficiency in Six Japanese Families

Abstract: Complete T4-binding globulin deficiency (TBG-CD) is inherited in an X-linked fashion. A nucleotide substitution has been shown to cause this hereditary condition in caucasians of French Canadian origin. Heterogeneity in molecular mechanisms for TBG-CD has also been reported. Genomic DNA from a Japanese male exhibiting TBG-CD was subjected to polymerase chain reaction, and the generated DNA fragments were sequenced. A single nucleotide deletion was found in the first base of the codon for amino acid 352 of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Further investigations will be needed to examine this possibility. Both the TBG-Kumamoto reported herein and the complete TBG deficiency in Japanese families shown by Yamamori et al [9] had the mutation near the carboxy-terminus on exon 4. From the results of these studies, it is suggested that the amino acid residues near the carboxy-terminus may be responsible for the intracellular processing of the TBG molecule.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…Further investigations will be needed to examine this possibility. Both the TBG-Kumamoto reported herein and the complete TBG deficiency in Japanese families shown by Yamamori et al [9] had the mutation near the carboxy-terminus on exon 4. From the results of these studies, it is suggested that the amino acid residues near the carboxy-terminus may be responsible for the intracellular processing of the TBG molecule.…”
Section: Discussionsupporting
confidence: 50%
“…Blood samples from her children were not analyzed, since we could not obtain any collaboration with them because of their young age. It was concluded that TBG-Kumamoto was a different familial type of TBG deficiency from those reported previously [5][6][7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Thus, the prevalence of TBG-PD having the same mutation should be studied. For complete TBG deficiency, we found only one kind of mutation of the TBG gene, a single nucleotide deletion in exon 4 of the TBG gene, in 18 unrelated Japanese families living in various areas [12]. It is noted that the same mutation was reported in a family with TBG-PD by Shirotani et al in an abstract form [20].…”
Section: Resultsmentioning
confidence: 61%